The Relationship between Nurses’ Work Environment Characteristics, Job Performance and Patients’ Satisfaction with Nursing Care - Filiz Özbey; Betül Sönmez (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This research aimed to examine the relationship between nurses’ work environment characteristics, their job performance and patients’ satisfaction with nursing care.Method: A cross-sectional, descriptive and correlational design was used. The study included 367 nurses working in internal medicine and surgical wards across three training and research hospitals in Istanbul, along with 538 inpatients. Participants were selected using a proportional quota sampling method. Data from nurses were collected using the Nurse Information Form, the Practice Environment Scale of the Nursing Work Index and the Task Performance Scale. Patient data were obtained using the Patient Information Form and the Newcastle Satisfaction with Nursing Care Scale. Descriptive statistics, intergroup comparison tests and correlation analyses were applied to examine the relationships among variables.Results: Nurses’ perceptions of their work environment were slightly above average while their self-reported job performance and patients’ satisfaction with nursing care were high. Patients’ satisfaction was higher in units where nurses worked an average of ≤45 hours per week, the nurse-to-bed ratio was ≤2 and nurses cared for ≤18 patients per shift (p<0.05). However, no significant correlations were found between nurses’ perceived work environment, their job performance and patients’ satisfaction with nursing care (p>0.05).Conclusion: This study identifies work-related characteristics of nurses that influence patients’ satisfaction with nursing care and provides useful findings for hospital administrators to improve patients’ satisfaction. It is recommended that administrators who wish to increase patients’ satisfaction ensure that the average weekly working hours of nurses, the nurse-to-bed ratio and the average number of patients cared for per shift are within ideal limits.